Metamorphoses of Aurora - Oguti, Takasi (1975)
P(論文) On the basis of the real time records of aurora by use of a highly sensitive TV camera at Syowa Station, Antarctica, classifications of appearance modes, patterns, and dynamics of auroras are attempted. The modes of appearance are classified into continuous appearance and intermittent appearance, patterns into sheet (or discrete arc), diffuse arc, smoke, striation, patch, and surface, and basic dynamics into splitting (or fold-over), fractional rotation, disruption and reconnection, meandering and folding, drift and propagation, on-off switching (or pulsation), and fading out. Among the 7 dynamical features, the splittings and rotations associated with rapid disruption and reconnections are found to be the most essential ones as the auroral activity proceeds, which leads to both the poleward and westward expansion of dusk aurora and the equatorward and eastward expansion of dawn aurora during an expansion phase. Rotation and folding-over of bright parts of aurora are concluded to be always clockwise viewed from below (viewed along the magnetic field). For example, splittings arise toward the right-hand side (clockwise curving protrusion from the primary sheet), bright spots rotate clockwise with trailing arms, active bright spots rotate with outward and clockwise streaming arms and small splittings such as ray structures unfold through a clockwise rotation of the split part. Rotation dominates in the region of a westward traveling surge or auroral bulge and poleward expanding arc, and consequently these regions are characterized by a chain of a strong clockwise vorticity or strong shear of drift, suggesting a rapid production of radial electric field in the magnetic tube of flux corresponding to these regions. It is pointed out that the clockwise splitting is the initial activation of aurora, and that the split part subsequently expands into a loop or a typical S-type structure as the luminosity increases at the expanding front. On the other hand, another typical pattern, the flame-like pattern, tends to ...